Procurement skills and procurement performance in public organizations: The mediating role of procurement planning - Ismail Abdi Changalima; Anjela Ewald Mdee (Cogent Business & Management)
Skills are important qualities that procurement practitioners should have because they are relevant to procurement activities. Given its significance, this study investigates the influence of procurement skills on procurement performance in public organizations in Tanzania. Furthermore, the study investigates the mediating effect of procurement planning on the relationship between procurement skills and procurement performance. A cross-sectional study was conducted, with data collected from public procurement practitioners in Dodoma City, Tanzania, using a structured questionnaire. To ascertain the hypothesized relationships, structural equation modeling was used. The findings indicate that procurement skills have a positive and significant influence on procurement performance in Tanzanian public organizations. Furthermore, procurement skills and procurement planning are significant and positively related and procurement planning significantly influences procurement performance. Finally, procurement skills have an indirect influence on procurement performance through procurement planning. The study concludes that procurement planning mediates the relationship between procurement skills and procurement performance. Therefore, procurement skills should be used to improve procurement planning in public organizations and procurement performance. In this regard, public organizations should ensure that practitioners are adequately trained to improve their skills in preparing and implementing procurement plans for improving procurement performance in their respective organizations.